Green GDP -- Research on the development of green GDP and ecological environment cost based on regression model - Chen, Zhiyi; Guo, Zixin; Wu, Ruirui (Transactions on Computer Science and Intelligent Systems Research, 2024)
This study explores the concept of green GDP and its relationship with eco-environmental cost, aiming to study the development of green GDP and eco-environmental cost based on regression model. First, green GDP is a new type of GDP after deducting the cost of resource and environment degradation and increasing environmental profit based on traditional GDP. Then, it introduces its accounting method to realize sustainable development by calculating resource and environmental cost and environmental benefit. It is found that the cost of resources and environment has an important impact on the growth of green GDP. Based on the regression model and SPSS statistical software, the complex nonlinear relationship between green GDP and environmental cost, resource depletion cost and environmental deterioration cost is quantitatively analyzed. Through multiple regression, it is concluded that the environmental pollution loss cost has a significant impact on green GDP, and the natural resource depletion cost is also one of the important factors. The results of this study help to better understand the relationship between the development trend of green GDP and the ecological environment cost, and provide theoretical support and policy suggestions for sustainable development.